Signal transduction pathways that function in both development and innate immunity. - Partridge, F; Gravato-Nobre, M; Hodgkin, J (2010)
C. elegans is developing in importance as a model for innate immunity. Several signaling pathways are known to be required for immune responses to a diverse range of pathogens, including the insulin signaling, p38 MAP kinase and transforming growth factor-beta pathways. These pathways also have roles during development, which can complicate the analysis of their functions in immunity. Recent studies have suggested that immunity in C. elegans is integrated across the organism by both paracrine and neuronal communication, showing the complexity of the immune system in this organism.